2015
DOI: 10.1093/arclin/acv081
|View full text |Cite
|
Sign up to set email alerts
|

How Localized are Language Brain Areas? A Review of Brodmann Areas Involvement in Oral Language

Abstract: The interest in understanding how language is "localized" in the brain has existed for centuries. Departing from seven meta-analytic studies of functional magnetic resonance imaging activity during the performance of different language activities, it is proposed here that there are two different language networks in the brain: first, a language reception/understanding system, including a "core Wernicke's area" involved in word recognition (BA21, BA22, BA41, and BA42), and a fringe or peripheral area ("extended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
137
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 233 publications
(154 citation statements)
references
References 53 publications
11
137
0
6
Order By: Relevance
“…Reflecting this, the average pars triangularis laterality measure was negative in both cohorts (HC laterality: −7.1±8.2, MDD laterality: −9.0±9.2, p -value = 0.18). The pars triangularis is part of the inferior frontal gyrus and, along with BA44, is considered part of Broca’s area, in which language processing occurs (Ardila, Bernal, & Rosselli, 2016). Interestingly, a recent meta-analysis using activation likelihood estimation (ALE) on 28 studies including 403 participants determined that the functional connectivity network of the inferior temporal gyrus (another critical language area) in healthy controls consists of the left prefrontal cortex (including BA45), the left insula, bilateral precuneus, cerebellum and occipital areas (as well as the left temporal lobe) (Ardila, Bernal, & Rosselli, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Reflecting this, the average pars triangularis laterality measure was negative in both cohorts (HC laterality: −7.1±8.2, MDD laterality: −9.0±9.2, p -value = 0.18). The pars triangularis is part of the inferior frontal gyrus and, along with BA44, is considered part of Broca’s area, in which language processing occurs (Ardila, Bernal, & Rosselli, 2016). Interestingly, a recent meta-analysis using activation likelihood estimation (ALE) on 28 studies including 403 participants determined that the functional connectivity network of the inferior temporal gyrus (another critical language area) in healthy controls consists of the left prefrontal cortex (including BA45), the left insula, bilateral precuneus, cerebellum and occipital areas (as well as the left temporal lobe) (Ardila, Bernal, & Rosselli, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…LIFGTri, along with the LIFG pars opercularis (BA44), is known to be involved in different steps of language production [38], namely, in syntactic encoding [39], speech praxis [40], and verb retrieval [41]. ACC is known to be involved in conflict and error monitoring, including domain-general control functions in healthy populations [42].…”
Section: Discussionmentioning
confidence: 99%
“…In other words, when L2 recovers, the coupling from LIFGTri to LIFGOrb decreases. These two regions are strongly anatomofunctionally interconnected as subregions of the inferior frontal gyrus [40]. LIFGTri is selected as the main language production area and LIFGOrb is a part of language-control network, which is involved in both language production and language-control processes (lexical semantic processes along with LIFGTri and selecting among lexical competitors) [44, 45].…”
Section: Discussionmentioning
confidence: 99%
“…Lemaire et al [11] proposed an "extended Broca's area" is activated in language production; Kadis et al [12] proposed an language production network; Bernal et al [13] proposed a Broca's network; and Ardila et al [14], in a meta-analytic review study, proposed a "Broca's complex or frontal language production system" including not only left BA44 and BA45, but also BA46, BA47, partially BA6 (mainly its mesial supplementary motor area) and extending subcortically toward the basal ganglia and the thalamus (Figure 1) [19]. Neuroimaging studies have also reported the participation of BA45 in language production in the following verbal functions: verbal fluency [20], grammar processing [19], phonological processing [21], lexical search [22], selective attention to speech [23], semantic memory retrieval [24] and reasoning processes [25].…”
Section: Neuroanatomy Of Language Productionmentioning
confidence: 99%
“…For example, neuroimaging studies have shown BA44 to be active in some other non-linguistic functions, such as action observation and motor acts, Figure 1. Broca's region according to Ardila et al, [14] includes BA44, BA45, BA46, BA47, mesial BA6 (supplementary motor area; not seen) and extending subcortically toward the basal ganglia and the thalamus (not seen). (Right panel) fMRI activation during speaking in a normal adult subject; observed is a wide activation including not only BA44 but also the surrounding areas, extending to the supplementary motor area (courtesy of the Department of Radiology-Nicklaus Children's Hospital).…”
Section: Neuroanatomy Of Language Productionmentioning
confidence: 99%